The Problem Based Learning Model And Learning Motivation On Results Study Word Woll Material At Slb-B Karya Mulia Surabaya - Ribut Kartikawati (Departement of Mathematics Education, 2024)
The aim of this research is to test the influence of the Problem Based Learning (PBL) model and learning motivation on results Studying Word Woll Material. This research used a True Experimental Design with a pretest-posttest control group design. The number of samples obtained was 90 students divided into 4 research classes, namely 45 students in Class 4 A and B SDLB-B as experimental samples and 45 students in Class 4 C and D SDLB-B as control samples. In carrying out statistical tests to test the hypothesis, in this case it will be carried out using the 2-way Anova analysis technique. Based on the data presentation and discussion above, several things can be concluded, as follows: (1) There are differences in results Learning Word Woll material between those taught using the Problem Based Learning (PBL) model, (2) There are differences in results Learning Word Woll material between those who have high learning motivation and those who have low learning motivation, and (3) There is an interaction between the learning model ( Problem Based Learning (PBL) model) and learning motivation on the results Studying Word Woll Material.